Hyperactive lesions of gingiva associated with severe alveolar bone loss: A rare finding - Tripathi, Amitandra Kumar (Contemp Clin Dent, 2015)
Pyogenic granuloma (PG) is an inflammatory reactive hyperplasia of connective tissue. It usually arises in response to various stimuli such as low-grade local irritation, traumatic injury, hormonal factors or certain kinds of drugs. It predominantly occurs in the second decade of life in young females and rarely may cause significantly alveolar bone loss. It managed by conservative surgical excision and removal of causative irritants. This paper presents the case of a PG in a 55-year-old male with severe alveolar bone loss in the affected site, managed by surgical intervention.